2017
DOI: 10.1021/acs.iecr.6b04913
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Organoclay Content on the Structure, Morphology, and Surface Related Properties of Novel Poly(dimethylsiloxane)-Based Polyurethane/Organoclay Nanocomposites

Abstract: Novel poly(dimethylsiloxane)-based polyurethane nanocomposites (TPU-NCs) were synthesized using in situ polymerization with the nanoclay, Cloisite 30B. DSC, TGA and DMTA analyses showed that TPU-NCs with organoclay content ≤5 wt % exhibited increased thermal stability, storage modulus and hard segment melt temperatures, but decreased degrees of crystallinity. TPU-NCs displayed increased surface hydrophilicity and enhanced surface free energy with increasing organoclay content. SWAXS confirmed intercalated form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
(202 reference statements)
3
11
0
Order By: Relevance
“…The PUC samples exhibited lower values (p-value < 0.001). The high contact angle of water on the PU membrane would indicate the hydrophobic properties of this polymer which is in agreement with some other studies [36,37]. A relatively high CH 2 I 2 contact angle indicates that the PU membrane is not a typical hydrophobic material.…”
Section: Surface Propertiessupporting
confidence: 91%
See 1 more Smart Citation
“…The PUC samples exhibited lower values (p-value < 0.001). The high contact angle of water on the PU membrane would indicate the hydrophobic properties of this polymer which is in agreement with some other studies [36,37]. A relatively high CH 2 I 2 contact angle indicates that the PU membrane is not a typical hydrophobic material.…”
Section: Surface Propertiessupporting
confidence: 91%
“…A thin layer of OC coming into contact with the liquid precursor efficiently adsorbed water together with other volatile compounds, which prevented the formation of microcavities on the surface of a composite. Similar changes were observed for PU composites with present OC in another study reporting the reduction of contact angles for water, as well as non-polar solvents [37]. The trends of increasing energies with dispersed OC were observed also for other polymers.…”
Section: Surface Propertiessupporting
confidence: 85%
“…25 This phenomenon may be caused from better directionally orientation of TPU chains and enhancement of melt crystallization aer importation of the exfoliated MMT layers and TPU matrix. 29 3.4. Mechanical properties of TPU nanocomposites 3.4.1.…”
Section: Thermal Behavior Of Tpu Compositesmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Numerous literatures on TPU nanocomposites pay great attention on the effect of methods of preparation, structure of polyurethane, microphase morphology, rheology, mechanical properties, thermal stability, etc. [21][22][23][24][25][26][27][28][29][30][31][32] Wang et al 33 rst reported the preparation of the polyurethane (PU)/clay nanocomposites, and concluded that large enhancements in tensile strength and modulus were possible even with intercalated clay particles. To take full advantage of these nanoscale MMT sheets, the key is to exfoliate and disperse the individual MMT layers within polymer matrices, which requires favorable organically modied MMT particles (OMMTs) interactions according to the thermodynamic theory.…”
Section: Introductionmentioning
confidence: 99%
“…The nanocomposite did not show any aggregation of graphene suggesting homogenous dispersion within the matrix. [ 38–40 ] However, TPU‐2.0 showed some bright spots on the surface, which could be graphene nanoplatelets either dispersed or aggregated nanoplatelets. From the EDS analysis, upon increasing the graphene loading the carbon content and oxygen content increased.…”
Section: Resultsmentioning
confidence: 99%